Wedge-tailed eagle - Olsen, Penny (Australian natural history series., 2005)
Australias Wedge-tailed Eagle belongs to the family of eagles, which together span the world. Eagles are powerful predators, with exceptional powers of flight and sight. They may kill to survive, but they also sleep, play, enjoy a bath, make tender parents, and form lasting relationships.